Performans yönetim sistemi - Astarlıoğlu, Esin (Fen Bilimleri Enstitüsü, 1997)
Performans Yönetim Sistemi; değişim ve gelişimi ancak çalışanları ile birlikte yakalayabileceğine inanmış organizasyonların kullandığı etkin sistemlerden birisidir. Tez çalışmasında Performans Yönetim Sistemi anlatılmış; organizasyonların insan kaynakları alanında uyguladıkları kariyer planlama, organizasyonel yedekleme, ücret ve ödül yönetimi sistemleri ile ilişkisi açıklanmıştır. Çeşitli firmaların sistemi nasıl ele aldıkları ve uyguladıkları incelenerek bir performans yönetim sistemi tasarlanmıştır. Çalışma öncelikle teorik olarak sistemi incelemiş, sistemin organizasyonlara ve çalışanlara getireceği faydalardan bahsetmiş, uygulama aşamalarını örneklerle açıklamaya çalışmıştır. Organizasyonların her birinin kendine ait bir kültürü, vizyonu, misyonu, değerleri ve hedefleri vardır. Her organizasyon kendi bünyesinde farklı değerleri öne çıkarmak ister. Bu nedenle olması gereken tek bir Performans Yönetim Sistemi yoktur. Ancak sistemin çatısı bellidir: Hedeflerin belirlenmesi, yıl içinde sürekli yönlendirme ve geri bildirim, değerlendirme ve gelişim planlamasıdır. Bu çatının üzerinde organizasyonlar kendilerine en uygun sistemleri yaratmalı ve uygulamalılardır.

Succeeding in a world of change, competition and information overload is challenging. Fortunately new technology and services emerge daily to assist individuals and organizations in meeting such challenges. Organizations are continuously influenced by changes in the environment around them, and in turn, organizations affect the outside environment. For today's organizations - whether large or small, government or private, profit or nonprofit, successful or not - change is one of few constants. From customers, competitors, distributors and suppliers to government regulations and fluctuating interest rates, organizations are surrounded by a myriad of factors which directly influence day-to-day operations. Likewise organizations can have a reciprocal effect on their external and internal environments. Therefore, leaders and organizations must vigorously prepare to not only cope, but to excel in the face of the challenges and demands of the world around them if they are to make an impact and remain successful. An organization of today, in order to be successful and competitive, expects to : - achieve performance objectives : mission, vision and strategy - achieve or surpass behavioral objectives - receive unstrained individual and group contribution - create ownership and commitment at all levels of the organization - breed and reap the fruit of creativity and innovation - develop individual and group talents and skills - broaden understanding and perspective within all levels of the organization - provide challenge and opportunity to each and every individual and team - create high levels of interdepence and synergy - create a "learning organization" culture To achieve all those expected results the organization should invest on its human resources. To have qualified human resources, the organization analyses their expectations and needs, and then creates methods to meet the results. Employee Surveys, done recently in some companies, show that people in the organizations, priorly, want; - to be aware of the mission, vision and strategies of the company, - to participate in setting the company goals and related to those goals set their own objectives, - training and development plans in accordance with their objectives, - to discuss their own performance with the managers, - to be able to draw their own career maps and - to earn a salary related to their contribution to the achievement of company objectives In order to meet those expectations; the organizations should begin to develop new methods or improve the existing ones. Performance Management is one of the methods needed in an organization that wants to excel. Performance Management can be defined as a process or set of processes for establishing shared understanding about what is to be achieved, and of managing and developing people in a way which increases the probability that it will be achieved. The overall aim of performance management is to establish a culture in which individuals and groups take responsibility for the continuous improvement of business processes, and of their own skills and contributions. Performance management systems can be used to communicate and reinforce the organization's strategies and values and to integrate individual and corporate objectives. They also enable individuals to express their own views on what they should be doing, where they should be going and how they should be managed. Also they let the expectations of managers and their staff to be shared. Managers can clarify their expectations of what they want their staff to do and staff can communicate their expectations on how they should be treated. Performance management operates as a partnership between the organization and the individual, in which both parties contribute to the definiton of objectives, tasks, standards and performance measures, monitoring progress, assessing and developing performance. The system operates in an ongoing cycle as: 1 ) Setting Objectives 2) Monitoring Progress 3) Assessing Performance 4) Individual Development Planning Before setting objectives mission, vision, values and strategy of the organization should be set in motion by people in the organization. When all the vm subunits of a larger organization - including subsidiaries, divisions, departments, plants, offices, work teams and individuals - develop and operate by their own individual but interrelated and mutually supportive mission statements, conditions for maximum effectiveness increase. The setting of objectives is the management process which ensures that every individual employee knows what role they need to play and what results they need to achieve to maximise their contribution to the organization. In essence it enables employees to know what is required of them and on what basis their performance and contribution will be assessed. Objectives should be jointly agreed in advance between the manager and the individual as both realistic and challenging and, as such, they are owned. The actual level of achievement should be measured so that the basis on which performance is assessed can be understood in advance. After the company objectives are set, they are cascaded to departmants, work teams and individuals. Objectives are agreed following discussions between managers and the individuals or teams responsible to them. Teams may have joint objectives, and individuals who work together can agree common or overlapping objectives. Besides objectives directly related to organization goals and key result areas; there may be objectives related to competences. Competence is the behaviour required of people to carry out their job effectively. Competences can be generic to all the jobs in the organization or specific to each job. Monitoring progress follows the objective setting. Individuals in the organization are constantly seeking to improve and feedback gives them the direction they need in order to self-correct. Indeed, consructive and meaningful feedback provides a source of help to anyone trying to progress. Feedback in performance management is always factual. It refers to results, events, critical incidents and significant behaviours which have affected performance in specific ways. Throughout the year there should be at least two formal performance reviews in order to monitor the progress. One may be "interim review" and the other " year end review". Also besides those formal reviews an ongoing monitoring should be done by the manager who acts as a coach. The performance review meetings are the basis for assessing the three key elements of performance contribution, competence and contiuous development. The review should be rooted in the reality of the employee's performance. It is concrete, not abstract and it allows managers and individuals together to take a positive look at how performance can be improved in the future and how any problems in meeting performance standards and achieving IX objectives can be resolved. There should be no surprises in a formal review if performance issues have been dealt with as they should have been, during the year, as they arise. During the "year end review"; the performance of the individual is assessed according to his/her objectives set at the beginning of the year. For the assessment the both parties should get prepared. The manager should review the objectives, standards, plans and competences agreed. Reference should be made to any notes made during or following interim review about the individual's performance. Then the manager decides on how well the individual has done in achieving his/her objectives; whether he/she is ready to take on additional responsibilities in the present job; whether the individual and the organization would benefit if they were provided with further experience in other areas of work; what direction the individual's career could take within the organization and what training or development the individual needs to help his/her work and/or to further his career with the organization. The individual, makes a self-assessment of his/her accomplishments; decides on training and development needs; thinks about his/her own expectations for the future in the organization and prepares his career plan. After the discussion of performance achieved by the employee during the year; the "Individual Development Plan" of the employee is prepared. This plan refers to both current job performance and the future career plans. Performance related pay is regarded as a method of improving performance which can be one of the processes of performance management but it is not a necessary process. Performance related pay links pay progression to a performance and/or competence rating. The rating could be carried out during a performance review or it could be conducted at a different time exclusively for performance related pay purpose. The thesis is written to highlighten all those aspects of the performance management. First the development of performance management in the business world are explained. After, the four main steps; setting objectives, monitoring progress, assessment and individual development planning are analysed. Following these parts the connection of performance management between career and succession planning; salary and reward management are explained. After explaining performance management and analysing its integration with other human resources methods; performance management systems from three firms - Fiat, Philip Morris and Arçelik are analysed and a new system is created and advised. The thesis shows that human resources are key elements in the organizations and to manage them effectively and gain their loyalty; they should be given more importance. They should contribute in defining both company objectives and their own objectives related to the company's. They should be assessed, rewarded, paid and trained according to their performance. Performance management is a process usefull both to the organization and to the employees. The human resources department can stimulate the introduction of a performance management system and facilitate its development. HR provides the training required and monitors its implementation. Fundamentally, however, a performance management system should be owned and driven by line managers and their staff.
Performance management
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Performans yönetimi; Performance management